2012
DOI: 10.1590/s0004-27302012000900009
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous puberty in girls with early diagnosis of Turner syndrome

Abstract: Objective: To verify if the frequency of spontaneous pubertal development among girls with Turner syndrome (TS) diagnosed in infancy and childhood is greater than that of patients diagnosed later. Subjects and methods: Thirty three girls aged < 10 years at the time of diagnosis were evaluated regarding pubertal development. The frequency of spontaneous puberty was compared with that of girls aged > 13 years diagnosed at the same service. Results: Sixteen of 32 informative patients had signs of spontaneous pube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
10
0
4
Order By: Relevance
“…Higher frequencies of spontaneous puberty were observed by Visser et al (), where 54% of their TS subjects older than 12 years had spontaneous breast development and 17% had a history of spontaneous menarche (Visser et al, ). Carpini et al () found that 6/16 TS girls had spontaneous pubertal development; there was no progression of puberty. They presented with breast development (until Tanner breast stage 2 [B2] in three cases, B3 in two, and B4 in one case), menarche occurred in 6 of the remaining 10 patients, with a mean age of 13.7 years (range: 12.0–15.8 years); the other 4 patients were aged 12.4–14.0 years (Carpini et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher frequencies of spontaneous puberty were observed by Visser et al (), where 54% of their TS subjects older than 12 years had spontaneous breast development and 17% had a history of spontaneous menarche (Visser et al, ). Carpini et al () found that 6/16 TS girls had spontaneous pubertal development; there was no progression of puberty. They presented with breast development (until Tanner breast stage 2 [B2] in three cases, B3 in two, and B4 in one case), menarche occurred in 6 of the remaining 10 patients, with a mean age of 13.7 years (range: 12.0–15.8 years); the other 4 patients were aged 12.4–14.0 years (Carpini et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Carpini et al () found that 6/16 TS girls had spontaneous pubertal development; there was no progression of puberty. They presented with breast development (until Tanner breast stage 2 [B2] in three cases, B3 in two, and B4 in one case), menarche occurred in 6 of the remaining 10 patients, with a mean age of 13.7 years (range: 12.0–15.8 years); the other 4 patients were aged 12.4–14.0 years (Carpini et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned studies ( 7 , 8 , 9 , 10 ) also describe cases in which estrogen replacement was required because full sexual maturation was not reached, despite the spontaneous onset of puberty. These findings indicate that there are many cases of incomplete ovarian function.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently known that up to 40% of TS girls may have some degree of spontaneous pubertal development and up to 19% may have complete puberty and menses [ 7 ]; these figures may be even higher when the sample is not biased towards patients with hypogonadism [ 25 ]. Thus, some patients with residual ovarian function may have normal gonadotropins levels throughout childhood and escape diagnosis when these hormones are measured.…”
Section: Discussionmentioning
confidence: 99%